Using the ACE survey to inform service development in a social care organisation: A case study - Kennedy, Mary (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2023)
In recent years implementation of the Adverse Childhood Experience (ACE) survey within social care organisations has steadily increased. Despite the sustained implementation, there is limited research on how and if ACE survey implementation informs social care service provision. This study employs a case study design to address this gap by examining the routine administration of the ACE survey by professionals working in family and early childhood education centres within the Daughters of Charity Child and Family Services (DoCCFS). The central research questions of the study examined workers' perspectives on what the transition to routine administration was like, and what impact, if any, administering the survey had on workers' relationships with service users and the pathways of care provided to them. The study also examined if and how the survey data was used to inform service provision within the social care organisation and if there were any differences in implementation and interpretation of the survey between the family and early childhood education workers. This study implemented a mixed-method research methodology. Qualitative data was collected from workers in semi-structured interviews and focus groups. In order to develop DoCCFS service user ACE profiles, aggregated quantitative data relating to ACE scores collected as part of a collaborative DoCCFS research project with the Trinity Research in Childhood Centre (TRiCC) was also examined. Compared to other research populations, the study determined ACEs were common for children and their parents and caregivers within the DoCCFS. It also established that although the overall experience of routine ACE survey administration was perceived as positive by workers, the implementation process resulted in several practical and emotional challenges for staff. The study further determined that translating ACE data into informing social care service delivery remains a work in progress. As there is a gap in the literature relating to ACE survey administration within social care settings, this study makes a significant contribution via the development of the PEAR implementation model. This model is based on the study's findings and is designed to help social care organisations considering the introduction of routine administration of the ACE survey.
APPROVED
Keywords: ACE survey; Implementation; Use of social epidemiology; Social care; Service provision; Adverse Childhood Experience; Inform service delivery; Worker perspectives